Both Charge-Regulation and Charge-Patch Distribution Can Drive Adsorption on the Wrong Side of the Isoelectric Point - Lunkad, Raju; Barroso da Silva, Fernando L; Košovan, Peter (Journal of the American Chemical Society, 2022)
The mechanism of protein-polyelectrolyte complexation on the wrong side of the isoelectric point has long puzzled researchers. Two alternative explanations have been proposed in the literature: (a) the charge-patch (CP) mechanism, based on the inhomogeneous distribution of charges on the protein, and (b) the charge-regulation (CR) mechanism, based on the variable charge of weak acid and base groups, which may invert the protein charge in the presence of another highly charged object. To discern these two mechanisms, we simulated artificially constructed short peptides, containing acidic and basic residues, arranged in a blocklike or alternating sequence. Our simulations of these peptides, interacting with polyelectrolytes, showed that charge patch and charge regulation alone can both lead to adsorption on the wrong side of the pI value. Their simultaneous presence enhances adsorption, whereas their absence prevents adsorption. Our simulation results were rationalized by following the variation of the charge regulation capacity and dipole moments of these peptides with the pH. Specifically for lysozyme, we found that charge patch prevails at physiological pH, whereas charge regulation prevails near the pI, thereby explaining seemingly contradicting conclusions in the literature. By applying the same approach to other proteins, we developed a general framework for assessing the role of the CP and CR mechanisms in existing case studies and for predicting how various proteins interact with polyelectrolytes at different pH values.